Boosting with Omicron-matched or historical mRNA vaccines increases neutralizing antibody responses and protection against B.1.1.529 infection in mice - Baoling Ying; Suzanne M. Scheaffer; Bradley Whitener; Chieh-Yu Liang; Oleksandr Dmytrenko; Samantha Mackin; Kaichun Wu; Diana Lee; Laura E. Avena; Zhenlu Chong; James Brett Case; LingZhi Ma; et al. (2022)
ABSTRACT The B.1.1.529 Omicron variant jeopardizes vaccines designed with early pandemic spike antigens. Here, we evaluated in mice the protective activity of the Moderna mRNA-1273 vaccine against B.1.1.529 before or after boosting with preclinical mRNA-1273 or mRNA-1273.529, an Omicron-matched vaccine. Whereas two doses of mRNA-1273 vaccine induced high levels of serum neutralizing antibodies against historical WA1/2020 strains, levels were lower against B.1.1.529 and associated with infection and inflammation in the lung. A primary vaccination series with mRNA-1273.529 potently neutralized B.1.1.529 but showed limited inhibition of historical or other SARS-CoV-2 variants. However, boosting with mRNA-1273 or mRNA-1273.529 vaccines increased serum neutralizing titers and protection against B.1.1.529 infection. Nonetheless, the levels of inhibitory antibodies were higher, and viral burden and cytokines in the lung were slightly lower in mice given the Omicron-matched mRNA booster. Thus, in mice, boosting with mRNA-1273 or mRNA-1273.529 enhances protection against B.1.1.529 infection with limited differences in efficacy measured.